Acute toxicity test of freeze dry super red dragon fruit (Hylocereus costaricensis) disclosing solutions: Study experimental - Yuslianti, Euis Reni; Dewi, Zwista Yulia; Al-wasi, Dimas Mohamad (Padjadjaran Journal of Dental Researchers and Students, 2024)
ABSTRACTIntroduction: Super red dragon fruit contains iron, vitamin C, Vitamin B1, B2, B12, and the color pigments betasianin and carotene. Betasianin and carotene have potential as natural plaque coloring agents (disclosing solution). The safety of the disclosing solutions made of super red dragon fruit has not been proven yet. The purpose of this study was to determine the safety of disclosing solutions agents made of freeze dried super red dragon fruit, through acute toxicity tests. Methods: This research method is an experimental laboratory using animals, with 48 male and female mice each. There are four treatment groups, namely the negative group, the group giving doses of 1250 mg/kgBW, 2500 mg/kgBW, and 5000 mg/kgBW. This acute toxicity test observed mortality, weight change, behavior change, and relative organ weight in mice. Data were analyzed using one way ANOVA test if (p>0.05) and Kruskal Wallis test for data (p<0.05). Results: The disclosing solution of super red dragon fruit did not cause death and toxic effects on mice, there were no significant differences in changes in body weight and behavior of mice, and there were significant differences in male organ indices including heart, lung, kidney and lymph organs. Conclusion: The administration of the disclosing solutions made of super red dragon fruit freeze dried in mice is safe and non-toxic based on acute toxicity tests.KEY WORDS: Disclosing solutions, super red dragon fruit, acute toxicity test.Uji toksisitas akut disclosing solutions buah naga super merah (Hylocereus costaricensis) freeze dry: Studi eksperimentalABSTRAKPendahuluan: Buah naga super merah memiliki kandungan zat besi, vitamin C, Vitamin B1, B2, B12, dan pigmen warna betasianin serta karoten. Betasianin dan karoten berpotensi untuk digunakan sebagai zat pewarna plak alami (disclosing solution), namun penggunaan disclosing solution buah naga super merah belum terbukti aman. Tujuan dari penelitian ini untuk mengetahui keamanan disclosing solution alami buah naga super merah freeze dry  melalui uji toksisitas akut. Metode: Metode penelitian ini adalah laboratorium eksperimental dengan menggunakan subjek penelitian hewan coba 48 ekor mencit jantan dan betina. Terdapat empat kelompok perlakuan yaitu kelompok negatif, kelompok pemberian dosis 1250 mg/kgBB, 2500 mg/kgBB, dan 5000 mg/kgBB. Uji toksisitas akut ini mengamati kematian, perubahan berat badan, perubahan perilaku, dan berat organ relatif pada mencit. Data dianalisis dengan menggunakan uji one way ANOVA apabila (p>0,05) dan uji Kruskal Wallis untuk data (p<0,05). Hasil: Disclosing solution buah naga super merah tidak menyebabkan kematian dan efek toksik pada mencit, tidak terdapat perbedaan bermakna pada perubahan berat badan dan perilaku mencit, serta terdapat perbedaan yang bermakna pada indeks organ jantan meliputi organ jantung, paru, ginjal dan limfa. Simpulan: Penggunaan bahan disclosing solution buah naga super merah freeze dry pada mencit aman dan tidak toksik berdasarkan hasil uji toksisitas akut.KATA KUNCI Disclosing solutions, buah naga super merah, uji toksisitas akut.